Gender Representation in English Textbooks for Islamic Junior High School Students - Fahriany Fahriany; Alek Alek; Ismail Suardi Wekke (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This article would investigate the gender representation in English textbooks for MTs Students. In detail, the investigation covered: Gender-biased, gender posistion, authors’ understanding, male and female position, the explicitly or implicitly presented the gender representation in the English textbook for MTs students. Critical Multimodal Analysis and Content Analysis Method was used to analyze the data. The results will be expected is to obtain the clear understanding of each aspects regarding to the gender representation in the English textbooks for MTs as the object of the investigated. Furthermore, another result can be summed up is the authors of English for MTs use imageare used inequal or unbalance. In other words, the authors of “English on Sky” Grade VIII for MTs/Junior High School shows that the gender positioning was inequal. In the meantime, the authors use some words to illustrate or depict the gender which are in English textbook “English in Focus”, they are adjective, proper name, and pronoun. Based on the result as seen above, the authors of the two English textbooks, not only the authors of English in Focus but also English on Sky have somewhat understanding the gender bias, gender streotype.